Avapritinib for advanced systemic mastocytosis: blood spotlight - Gotlib, Jason; Reiter, Andreas; DeAngelo, Daniel J. (Blood, 2022)
Avapritinib, a highly selective inhibitor of KIT D816V, was approved by the Food and Drug Administration in 2021 for treatment of advanced systemic mastocytosis (AdvSM) and by the European Medicines Agency in 2022 for AdvSM after prior systemic therapy. The phase 1 EXPLORER and phase 2 PATHFINDER trials demonstrated that avapritinib can elicit complete and durable clinical responses and molecular remission of KIT D816V. Key management challenges relate to the complex mutational landscape of AdvSM, often found with an associated hematologic neoplasm.
Gesehen am 24.09.2024